Prevalence and relationships of dating application usage, cyber-fraud and mental health among emerging adults in Hong Kong - Chee-kit Chan; Xin Wang; Xue Yang (Psychiatry Research Communications)
This study aimed to investigate the prevalence and relationships of cyber fraud on dating applications and mental health among emerging adults. An online survey was conducted in Hong Kong (n = 401). Results showed that 32% of the dating application users encountered cyber-fraud in the last 2 weeks. Users encountering cyber-fraud had significantly poorer mental health than non-victim users and non-users. Education levels, being female, financial loss, and the leakage of private information were positively related to mental health problems of cyber-fraud victims. Education programs and supporting services are warranted to enhance youth's awareness and minimize the detrimental effects caused by cyber fraud.